The BCGΔBCG1419c Vaccine Candidate Reduces Lung Pathology, IL-6, TNF-α, and IL-10 During Chronic TB Infection - Flores-Valdez, Mario A.; Pedroza-Roldán, César; Aceves-Sánchez, Michel de Jesús; Peterson, Eliza J. R.; Baliga, Nitin S.; Hernández-Pando, Rogelio; Troudt, JoLynn; Creissen, Elizabeth; Izzo, Linda; Bielefeldt-Ohmann, Helle; Bickett, Thomas; Izzo, Angelo A. (Frontiers in Microbiology, 2018)
Mycobacterium tuberculosis (M. tuberculosis), the causative agent of human tuberculosis (TB), is estimated to be harbored by up to 2 billion people in a latent TB infection (LTBI) state. The only TB vaccine approved for use in humans, BCG, does not confer protection against establishment or reactivation from LTBI, so new vaccine candidates are needed to specifically address this need. Following the hypothesis that mycobacterial biofilms resemble aspects of LTBI, we modified BCG by deleting the BCG1419c gene to create the BCG BCG1419c vaccine strain. In this study, we compared cytokine profiles, bacterial burden and lung lesions after immunization with BCG or BCG BCG1419c before and after six months of aerosol infection with M. tuberculosis H37Rv in the resistant C57BL/6 mouse model. Our results show that in infected mice, BCG BCG1419c significantly reduced lung lesions and IL-6 in comparison to the unmodified BCG strain, and was the only vaccine that decreased production of TNF and IL-10 compared to non-vaccinated mice, while vaccination with BCG or BCG BCG1419c significantly reduced IFN- production. Moreover, transcriptome profiling of BCG BCG1419c suggests that compared to BCG, it has decreased expression of genes involved in mycolic acids metabolism, and antigenic chaperones, which might be involved in reduced pathology compared to BCG-vaccinated mice.